Anti-inflammatory and uric acid lowering effects of Euodiae fructus on hyperuricemia and gout mice - Zhilei Wang; Zhilei Wang; Jingwen Liu; Yu Mou; Wenhao Liao; Yuchen Li; Juan Liu; Jianyuan Tang; Jianyuan Tang (Frontiers in Pharmacology, 2024)
The metabolic disease hyperuricemia (HUA) is caused by presence of excessive serum uric acid (UA), which leads to an increased risk of chronic kidney disease and gout. As a widely used traditional Chinese medicine, Euodiae fructus (ER) has strong anti-inflammatory and analgesic effects, however, its therapeutic effects on HUA and gout have not been investigated. To investigate the potential effects and underlying mechanisms, the effect of ER on proinflammatory cytokines and NLRP3 inflammasome activation was studied in mouse bone marrow macrophages. Moreover, a mouse model of HUA and gouty arthritis was established by coadministration of potassium oxonate (PO) and monosodium urate crystals to mice fed a high-fat diet (HFD) for 37 consecutive days. Oral administration of ER aqueous extract was given 1 hour later after the injection of PO for 10 days. Our study showed that ER is a powerful NLRP3 inhibitor in mouse macrophages. Most importantly, ER (0.75 g/kg) treatment substantially decreased the ankle joint thickness ratio, serum UA, creatinine and blood urea nitrogen levels (p < 0.05). Additionally, ER (0.75 g/kg) dramatically reversed the increases in renal urate transporter 1 (URAT1) and glucose transporter 9 (GLUT9) as well as the decreases in organic anion transporter 1 (OAT1) and ATP binding cassette subfamily G member 2 (ABCG2) levels (p < 0.05). Moreover, ER (0.75 g/kg) markedly ameliorated the production of the serum inflammatory cytokines IL-1β and TNF-α (p < 0.01), and improved the activation of NLRP3 inflammasome signaling in the kidneys. Taken together, these data indicate that ER, a powerful and specific NLRP3 inhibitor, has multiple anti-HUA, anti-gout and anti-inflammatory effects. Our investigation is designed to experimentally support the conventional use of ER-containing classical herbal formulas in the treatment of HUA-related disorders and may add a new dimension to the clinical application of ER.